Mitigating Discrimination and Privacy Threats in Algorithmic Pricing through Personal Data Protection Law in Indonesia - Aprilinda, Dias Rizki (Estudiante Law Journal, 2025)
This research is motivated by the legal ambiguity in Article 34 paragraph (2) letter (a) of Law Number 27 Year 2022 on Personal Data Protection (PDP Law), especially related to the lack of clarity in interpreting the element “automatically” stipulated in the article towards algorithmic pricing. Basically, the article has an important role in preventing problems arising from algorithmic pricing in the form of privacy threats and price discrimination. The purpose of this research is to analyze whether the characteristics of algorithmic pricing can be categorized as an automatic decision under PDP Law and to analyze the recommendation of the appropriate regulatory substance related to automatic decisions in PDP Law against algorithmic pricing. The research method used is juridical-normative by using legislative approach and comparative approach. The result of this study found that algorithmic pricing cannot be categorized as an automatic decision under PDP Law. Therefore, Indonesia can establish an automated decision guideline issued by the Ministry of Digital and Information by referring to the Guidelines on Automated Individual Decision-Making and Profiling for the Purposes of Regulation 2016/679 issued by the Article 29 Working Party in the European Union.